THE IMPACT OF TECHNOLOGY TRANSFER ON SESAME EXPORT COMPETITIVENESS: INSIGHTS FROM TURKEY AND UZBEKISTAN - Murat AYDIN; Metin TETİK (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
This study examines the trade relationship between Turkey and Uzbekistan, particularly in sesame exports, with the aim of strengthening Uzbekistan's competitiveness. Based on the theory of comparative advantage and using key indicators such as the Revealed Comparative Advantage (RCA) Index, the Revealed Symmetric Comparative Advantage (RSCA) Index, and the Normal Revealed Comparative Advantage (NRCA) Index, this study highlights the robust competitiveness of Turkey in exporting agricultural machinery designed specifically for sesame production. Through a comprehensive analysis of these indices, the study highlights Turkey's particular strength in this sector, sheds light on its comparative advantage and emphasises the country's strategic position in the global market for sesame-related agricultural machinery. However, Uzbekistan currently lacks competitiveness in sesame exports. The study underlines the key role of effective technology transfer, especially in machinery exports from Turkey, in improving Uzbekistan's position. Econometric models show the significant impact of exchange rates and domestic demand on Uzbekistan's sesame exports. The study's findings highlight ways to improve the efficiency of agricultural machinery exports between the two countries. This provides policymakers with valuable insights to strengthen sustainable trade relations and increase the volume of agricultural exports.